Pengaruh Terapi Musik Klasik Terhadap Tingkat Kecemasan Ibu Hamil Trimester III - Grace Erlyn Damayanti S; Riris Sitorus; Desika Wali Pardede; Luci Riani Ginting; Pitriani P (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
In a woman's life cycle, pregnancy is a very sensitive period. During pregnancy, hormonal changes occur as a result of the mother's body adapting to the growth and development of the fetus in her womb. These changes will result in physical and psychological changes in the mother during pregnancy. During pregnancy, the fetus is alive and developing in preparation for life outside the womb, as well as pregnant women must prepare for the birthing process. Physiological adaptations during pregnancy that occur in pregnant women will prepare them for birth and becoming a mother. However, if there is no good self-management, physical and psychological changes during pregnancy can become a stressor for the mother. This can cause anxiety in pregnant women. The anxiety experienced by mothers during pregnancy can result in changes in physical activity, nutrition and sleep. This can have an impact on changes in the mother's mood and fetal development. This study aims to see the effect of classical music therapy on the anxiety level of pregnant women in the third trimester. The research is a Quasi Experiment with pre test and post test design. The population in this study were all third trimester primigravida pregnant women with a gestational age of â‰¥ 28 weeks. The sample obtained was 19 people using purposive sampling technique. The data was tested using a paired sample t test with a confidence level of 95%. Research shows that classical music therapy has an effect on the anxiety level of pregnant women in the third trimester with a p value of 0.000. It is hoped that the Community Health Center can implement and provide information on the provision of classical music therapy as a therapy to reduce anxiety levels in third trimester pregnant women.